Mechanics of Biological Tissue - Holzapfel, Gerhard A.; Holzapfel, Gerhard A.; Ogden, Ray W.; Ogden, Ray W. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The mechanics of biological tissues is a multidisciplinary and rapidly expanding area of research. This book highlights some important research directions that combine mechanical sciences with exciting new developments in biology. It includes state-of-the-art articles on: Tissue growth and remodelling – general continuum theories of growth, remodelling and adaptation, with specific applications to arterial, tendon and cartilage growth and to bone healing. Micromechanics, cells and matrix – measurements of the mechanical properties of cells, engineering of cell systems, constitutive and computational modelling of cells and cell-substrate interactions, and the transition from microscopic modelling to its macroscopic consequences. Arteries in health and disease – analysis of residual stress and its development, modelling the constitutive properties of arterial walls, computational analysis of the effect of stenting on the arterial wall, studies of collagen fibre distributions in saccular aneurysms and the interaction between blood flow and aneurysm development. Biological tissues – the musculo-skeletal system, heart valves, ligaments, intervertebral discs, the uterus and vocal fold tissues, with experimental, modelling and computational perspectives. Image-based analysis – illustration of imaging techniques that have great potential for the analysis of tissue properties and pathologies and for guiding the design of engineered tissue constructs. This collection of papers should be of interest to theoretical, computational and experimental researchers and doctoral students in the area of biomechanics and in related areas of engineering, biology and medicine.